Practicing multi-sited ethnography - Della Puppa, Francesco (Dve domovini, 2024)
The article illustrates the multi-sited use of the ethnographic method and the narrative in-depth interview in research on transnational migration between Bangladesh and Italy. Assuming a Sayadian perspective, the author explores the ways of accessing the transnational research field, the dynamics of anticipatory socialization at the interview within the transnational space, and the opportunity for collective self-socio-analysis and construction of a family memory that an in-depth interview implies. Finally, the article deepens the implications that the use of linguistic translators entails in ethnographic work and interpretative research.
Keywords: Bangladeš; etnografija; medjezikovno posredovanje; metodologija; migracije; poglobljeni intervjuji; refleksivnost; transnacionalizem; večprizoriščna etnografija